Influence of Harmonics Voltage on MOSA Current Extraction Methods - Plaengpraphan, Chorphaka; Tanthanuch, Nutthaphong (Frontiers in Engineering Innovation Research, 2020)
The most common monitoring method of metal–oxide surge arrester is based on leakage current measurement, particularly, the component of resistive leakage current. Nowadays, there are several analytical methods used to extract the resistive leakage current. These analytical methods need both current and voltage signals. However, in fact, electrical system voltage contains harmonics and because of these harmonics, it may affect the accuracy of resistive leakage current extraction methods in different ways. The calculated results may be in error or incorrect. It can lead to erroneous evaluation or fault assessment. This paper compares the extracted results both amplitude and signal between three different methods; improve compensation method, harmonic analysis method and current orthogonality method. The results have showed that voltage harmonics not affect resistive leakage current amplitude. However, they have an effect on current waveforms. The waveshapes obtained from different methods are not the same. Current orthogonality method gives the most accurate results because its algorithm calculates current on all frequencies and includes non-linear behavior of metal oxide material.